In between 21st century skills and constructivism in elt: Designing a model derived from a narrative literature review - Orak, Suheyla Demirkol; Al-Khresheh, Mohammad H. (Sciedu Press, 2021)
While the 21st-century demands the learners to be technologically competent and self-driven to cope with technological advancement, the educational practitioners find it challenging to prepare the young learners to keep pace with this demand. However, in doing so, to prepare the learners as adaptable to the 21st-century demands, constructivism can be envisaged as the most time-appropriate and updated theory of the teaching-learning process, compared to other approaches. Specifically, because one of the requirements from the learners of the 21st-century is to be self-driven and take ownership of the learning, constructivism is the closest theory to achieve this goal. This position paper aims to build a procedural link within 21st-century expectations and its cooperation with the constructivist learning approach. The paper also offers a design for constructivist teaching in ELT classrooms in the 21st-century and defines the role of teachers and students, as established by the literature. © 2021 Elsevier Masson SAS. All rights reserved.
Keywords: 21; Andragogy and ELT; Constructivism and ELT; Heutagogy and ELT